Evaluation of betulin mutagenicity by Salmonella/microsome test - Yoshida, Edson Hideaki; Tribuiani, Natália; Sabadim, Giovana; Moreno, Débora Antunes Neto; Varanda, Eliana Aparecida [UNESP]; Oshima-Franco, Yoko (Maad Rayan Publishing Company, 2016)
Purpose: Betulin is a pentacyclic triterpene found in the outer barks of innumerous plants. This secondary metabolite is easily isolated from plants with the major interest in converting it to betulinic acid, which pharmacological properties were much more exploited than betulin. But, investments in the own betulin have been grown since no chemical step is necessary. In this study we focused the precursor betulin in order to evaluate its mutagenicity by Salmonella/microsome assay (Ames test). Methods: The Ames test was carried out using a commercial betulin exposed to Salmonella typhimurium strains TA98, TA100, TA102, and TA97a, in experiments with (+S9) and without (-S9) metabolic activation. Results: Betulin was unable to increase the number of revertants (+S9 and -S9 metabolic activation) showing the absence of any mutagenic effect by Ames test. Conclusion: This study allowed attribute safety to betulin being important for exploiting its pharmacological uses.
Keywords: Ames test; Betulin; Salmonella mutagenicity; Triterpenoid